ANALISIS DAMPAK KEBIJAKAN ALOKASI DANA OTONOMI KHUSUS BIDANG PENDIDIKAN DAN KESEHATAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI PAPUA - Virgie Delawillia Kharisma; Palupi Lindiasari Samputra; Payiz Zawahir Muntaha (Universitas Halu Oleo, 2020)
This study aims to assess the impact of the Special Autonomy Fund in Papua Province on the Human Development Index measured through the allocation of the Special Autonomy Fund in education and health. The government is trying to accelerate the development of Papua, one of which is through the Special Autonomy Fund. This study uses a quantitative approach with panel data regression, covering: 2014-2017 data in 29 districts/cities in Papua Province, each variable, namely: HDI, GRDP per Capita, Allocation of Special Autonomy Funds in Education, Allocation of Special Autonomy Funds in Health and poverty level. The results of the study concluded that the Special Autonomy Fund did not have a significant effect on increasing the Human Development Index in Papua Province in 2014-2017. Strategic efforts in development in Papua are needed not only through the distribution of the Special Autonomy Fund, but also the enhancement of the capacity of the apparatus, evaluation of the method of channelling and utilizing the Special Autonomy Fund, and other policies with a local wisdom approach.